Infrared image monitoring of local anesthetic poisoning in rats - Carstens,Angelo Manoel G. (2016)
Abstract Background and objectives: To evaluate the thermographic predictive value of local anesthetic poisoning in rats that indicates the early recognition of thermal signs of intoxication and enable the immediate start of advanced life support. Methods: Wistar rats underwent intraperitoneal injection of saline and ropivacaine; they were allocated into pairs, and experiments performed at baseline and experimental times. For thermography, central and peripheral compartment were analyzed, checking the maximum and average differences of temperatures between groups. Thermographic and clinical observations were performed for each experiment, and the times in which the signs of intoxication occurred were recorded. In the thermal analysis, the thermograms corresponding to the times of interest were sought and relevant data sheets extracted for statistical analysis. Results: Basal and experimental: the display of the thermal images at times was possible. It was possible to calculate the heat transfer rate in all cases. At baseline it was possible to see the physiology of microcirculation, characterized by thermal distribution in the craniocaudal direction. It was possible to visualize the pathophysiological changes or thermal dysautonomias caused by intoxication before clinical signs occur, characterized by areas of hyper-radiation, translating autonomic nervous system pathophysiological disorders. In animals poisoned by ropivacaine, there was no statistically significant difference in heat transfer rate at the experimental time. Conclusions: The maximum temperature, medium temperature, and heat transfer rate were different from the statistical point of view between groups at the experimental time, thus confirming the systemic thermographic predictive value.